Serum mRNA levels of cytokeratin-19 and vascular endothelial growth factor in oral squamous cell carcinoma and oral potentially malignant disorders using RT-PCR - Kalpani Senevirathna; Thilini Anupama Nanayakkarawasam Mahakapuge; Nadeeka U. Jayawardana; Jayanthe Rajapakse; Chandrika Udumalagala Gamage; Bimalka Seneviratne; Unil Perera; Kehinde Kazeem Kanmodi; Ruwan Jayasinghe (BMC, 2024)
Abstract Background Oral cancers, which include tumors of the oral cavity, salivary glands, and pharynx, are becoming increasingly prevalent worldwide. Squamous cell carcinoma accounts for over 90% of malignant oral lesions, with oral squamous cell carcinoma (OSCC) being notably common in the Indian subcontinent and other regions of Asia. This is especially true in South-Central Asia, including Sri Lanka, where it is particularly prevalent among men. This study aims to evaluate the levels of Vascular Endothelial Growth Factor-A (VEGF-A) and Cytokeratin-19 (CK-19) mRNAs in whole blood as a potential method for the early detection of OSCC. Methods The study included 40 patients (each from OSCC, Oral Submucous Fibrosis (OSF), Oral Leukoplakia (OLK), Oral Lichen Planus (OLP), and 10 healthy controls. The expression levels of VEGF-A and CK-19 mRNAs were measured from extracellular RNA extracted from whole blood samples using real-time reverse transcription polymerase chain reaction (RT-PCR) with sequence-specific primers. Receiver operating characteristic (ROC) curve analysis was used to evaluate the effectiveness of these biomarkers in detecting OSCC. Results The results demonstrated a significant increase in blood transcripts of the candidate mRNAs CK-19 and VEGF-A in patients with OSCC, OSF, OLK, and OLP. The Wilcoxon signed-rank test revealed a p-value of 0.002 for each specific comparison between diseased patients and healthy controls (i.e., OSCC vs. HC, OSF vs. HC, OLP vs. HC, OLK vs. HC) for both CK-19 and VEGF-A. When these two biomarkers were used together, they provided a 60% predictive probability for patients with OSCC (p = 0.023). Conclusion This study highlights the efficacy of blood mRNA transcriptome diagnostics in detecting OSCC. This innovative clinical approach has the potential to be a robust, efficient, and reliable tool for early cancer detection. Blood-based transcriptomes could be further explored for their effectiveness in various health contexts and for routine health monitoring.